2016
DOI: 10.1093/infdis/jiw070
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial Blue Light Inactivation of Gram-Negative Pathogens in Biofilms: In Vitro and In Vivo Studies

Abstract: aBL has antimicrobial activity in biofilms ofA. baumannii and P. aeruginosa and is a potential therapeutic approach for biofilm-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
104
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 44 publications
3
104
0
1
Order By: Relevance
“…Our group performed studies of aBL inactivation of P. aeruginosa and A. baumannii biofilms using bioluminescent strains (Wang et al, 2016). Biofilms were formed by incubating bacterial suspensions in 96-well microtiter plates for 24 to 72 h. Viability of bacterial cells in biofilms were quantified based on the bacterial luminescence.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group performed studies of aBL inactivation of P. aeruginosa and A. baumannii biofilms using bioluminescent strains (Wang et al, 2016). Biofilms were formed by incubating bacterial suspensions in 96-well microtiter plates for 24 to 72 h. Viability of bacterial cells in biofilms were quantified based on the bacterial luminescence.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…P. aeruginosa (Dai et al, 2013b; Wang et al, 2016), A. baumannii (Wang et al, 2016; Zhang et al, 2014) and C. albicans (Zhang et al, 2016) were investigated by using fluorescence spectroscopy or HPLC analysis. All results implied the presence of endogenous porphyrins and/or flavins in the microbial cells.…”
Section: Mechanism Of Action Of Antimicrobial Blue Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…14,23,25,26,30,35 It was also observed that pathogenic microbes are less able to develop resistance to aBL than to conventional antibiotics. Our group recently performed several studies by exposing Pseudomonas aeruginosa, 25 Acinetobacter baumannii, 28 Candida albicans 27 or Escherichia coli (unpublished), to repeated cycles of sub-lethal aBL.…”
mentioning
confidence: 99%
“…25,27,28 Other studies demonstrated that aBL did not cause significant damages to host cells and did not impair wound healing. 18,26,28,34,39,40 In this issue of Virulence, Fila et al 22 investigated the effectiveness of aBL inactivation of Pseudomonas aeruginosa using a panel of wide types and clinical strains, including multidrug-resistant and extensively drug-resistant strains. In agreement of previous studies, the authors found that aBL exerted significant antimicrobial effect on all Pseudomonas aeruginosa strains tested, resulting in 5.2-to 8-log 10 reduction of colony forming units (CFU).…”
mentioning
confidence: 99%